Approach of Homoeopathy to Addiction of Harmful Substances (Homoeopathy for All, 2024)
Addiction or substance dependence  or neuropsychiatric disorders are  characterized by the desire to  take more drugs despite the mild  problems that occur. It is a problem  that affects people's brain and  behaviour , leading to the inability  to control the use of legal or illegal  drugs. Substances such as alcohol,  marijuana and nicotine are also  considered drugs. In the case of drug  addiction, homeopathic remedies  can be effective in relieving  symptoms and preventing addiction.
Keywords: Alcohol; cigarette; alcohol dependence; drug addiction; homeopathy